Using Health Belief Model to Prevent Skin Cancer among Farmers - Reza Sadeghi; Narges Khanjani; Mehri Hashemi; Mohammad Movagheripour (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: Skin cancer is the most frequent malignancy in Iran. Exposure to excessive ultraviolet radiation is an important risk factor in creating skin tumors. This study was conducted to determine the effectiveness of the Health Belief Model (HBM) on the health education of Farmers in Sirjan. Methods: This study was a quasi-experimental study. Two hundred Farmers attending health centers in Sirjan city, were selected to participate in this study (100 in intervention group and 100 in the control group). The intervention was conducted over two sessions in 60 minutes. Data were collected by a validated and reliable questionnaire (49 questions) before intervention and three months after the intervention. Data was analyzed by chi-square, Fisher's exact, paired t-tests and independent t-test. Results: After intervention, knowledge scores increased significantly in both intervention and control group, which was probably due to the routine education program in that center. Perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy increased significantly in the intervention group (p<0.001). But, there was no increase or significant difference in the control group. Conclusion: HBM was effective in educating the Farmers. Therefore, it is proposed to use HBM along with the traditional training methods in training farmers. Paper Type: Research Article